Disrupted functional connectivity between visual and emotional networks in psychosis risk syndromes through representational similarity analysis - Ruan, Xi; Zhang, Lang; Duan, Mingjun; Yao, Dezhong; Luo, Cheng; He, Hui (Frontiers in Psychiatry, 2025)
Schizophrenic individuals experience a prolonged prodrome before their first episode, often referred to as Psychosis Risk Syndromes (PRS). The PRS is characterized by non-specific symptoms, yet the underlying neural mechanisms remain unclear. Representational similarity analysis (RSA) has proven effective in elucidating the relationships between different data modalities. This approach could provide valuable insights into the functional coupling between sensory perception and emotion in PRS subjects. In this study, there were 27 PRS subjects and 33 control subjects. Neuropsychological assessments were conducted to evaluate the participants’ recent mental states and their risk of mental illness. Each subject underwent task-based functional magnetic resonance imaging (fMRI), which included steady-state visual evoked potentials (SSVEP) and expression matching tasks. The areas of brain activity were defined as regions of interest (ROIs). RSA was used to calculate the relationships between the SSVEP and expression matching tasks. In the functional coupling between the SSVEP at 5 Hz and 10 Hz conditions, the PRS group showed lower functional coupling in the fusiform area compared to controls. Additionally, in the functional coupling between the SSVEP at 10 Hz and the emotion matching conditions, the PRS group demonstrated decreased activation in visual regions compared to controls. Overall, our findings suggest that PRS subjects exhibit diminished functional couplings between basic visual stimuli and vision-emotion matching tasks, indicating abnormal visual processing in both the primary visual cortex and more advanced stages of information processing.